1998
DOI: 10.1073/pnas.95.17.9985
|View full text |Cite
|
Sign up to set email alerts
|

An 85-kb tandem triplication in the slow Wallerian degeneration ( Wld s ) mouse

Abstract: Wallerian degeneration is the degeneration of the distal stump of an injured axon. It normally occurs over a time course of around 24 hr but it is delayed in the slow Wallerian degeneration mutant mouse (C57BL͞Wld s ) for up to 3 weeks. The gene, which protects from rapid Wallerian degeneration, Wld, previously has been mapped to distal chromosome 4. This paper reports the fine genetic mapping of the Wld locus, the generation of a 1.4-Mb bacterial artificial chromosome and P1 artificial chromosome contig, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
127
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(130 citation statements)
references
References 33 publications
1
127
0
Order By: Relevance
“…The Wld S mouse strain displays a phenotype of slow Wallerian degeneration due to spontaneous mutation on chromosome 4 (Lyon et al, 1993) that is intrinsic to axons (Lunn et al, 1989;Perry et al, 1990) and is identified as an 85-kb tandem triplication (Coleman et al, 1998) that translates into a neuroprotective chimeric fusion protein of ubiquitin assembly factor E4B (Ube4b) and mononucleotide adenylyltransferase (Nmnat) (Conforti et al, 2000). Using the model of Wld S degeneration, we found a positive correlation between TNFα and MMP-9 expression and the macrophage migration capacity of injured nerve.…”
Section: Discussionmentioning
confidence: 99%
“…The Wld S mouse strain displays a phenotype of slow Wallerian degeneration due to spontaneous mutation on chromosome 4 (Lyon et al, 1993) that is intrinsic to axons (Lunn et al, 1989;Perry et al, 1990) and is identified as an 85-kb tandem triplication (Coleman et al, 1998) that translates into a neuroprotective chimeric fusion protein of ubiquitin assembly factor E4B (Ube4b) and mononucleotide adenylyltransferase (Nmnat) (Conforti et al, 2000). Using the model of Wld S degeneration, we found a positive correlation between TNFα and MMP-9 expression and the macrophage migration capacity of injured nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, molecular mechanisms involved in axon pruning in Drosophila share similarities with Wallerian degeneration in vertebrates. Wallerian degeneration is thought to be mediated by an intrinsic mechanism of axon self-destruction (Avery et al 2009;Coleman et al 1998;Conforti et al 2000;Lunn et al 1989;Mack et al 2001), which also involves the ubiquitin-proteosome system Zhai et al 2003).…”
Section: Guidance Molecules In Axon Pruning Intrinsic and Extrinsic Fmentioning
confidence: 99%
“…6 Our groups showed that the gene identified by positional cloning [12][13][14] delays Wallerian degeneration in transgenic mice and virally transduced dorsal root ganglion (DRG) explant cultures. 15,16 Wld S encodes a fusion protein containing 70 N-terminal amino acids of ubiquitination factor Ube4b, full-length nicotinamide adenine dinucleotide (NAD þ )-synthesising enzyme nicotinamide mononucleotide adenylyltransferase 1 (Nmnat1), and a unique 18-amino-acid joining sequence.…”
mentioning
confidence: 99%